(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
The article emphasizes that the international community is an area of free expression by citizens of their potential, consisting of voluntary organizations and associations and free from government interference. Social movements, mass media, political parties, trade unions, public associations, non-governmental non-profit organizations, citizens’ self-government bodies, creative associations are institutions of civil society. The article also emphasizes that one of the features of civil society is that membership in all public organizations of the non-state system must be voluntary